PRACTICE OF PROPER HANDWASHING AND ITS ASSOCIATED FACTORS AMONG STAFF IN A MALAYSIAN UNIVERSITY - Oo, San San; Ibrahim, Mohd Salami; Thwe Aung, Myat Moe; Mohd Yusop, Yuzana; Hassan, Azmi; Naing, Nyi Nyi; Mohd Amin, Rahmah; Abd Aziz, Aniza; Nik Mahdi, Nik Nor Ronaidi (Malaysian Journal of Public Health Medicine, 2021)
In higher education setting throughout the world, the practise of handwashing among staff is essential, particularly in the period of COVID-19 pandemic. Despite the overwhelming evidence on the effectiveness of proper handwashing, the knowledge, attitude and practice of handwashing among the staff of higher education have not been well investigated. Consequently, a cross-sectional study among staff in a university in Malaysia was conducted to identify the prevalence of proper handwashing and its associated factors. The data was collected using questionnaires in Google form from 18th June to 21st June 2020. Statistical analyses involved simple and multiple logistic regression with backward likelihood ratio method. Out of 349 participants, 31.8% (95% CI: 26.9,36.7) had proper handwashing practice. The results of the multivariable analysis revealed that the total knowledge scores (OR: 1.04, 95% CI: 1.001, 1.071) and the total attitude scores (OR: 1.23, 95% CI: 1.152, 1.321) were found to be significantly associated with proper handwashing practice among staff. Our study suggests that having the right knowledge and favourable attitudes are crucial towards achieving the proper handwashing practise. Additional supports for promoting a conducive ecosystem may also likely be needed to sustain a long-term practice of proper handwashing.